COMBINATION OF PENETRATION AND PYLORIC AND DUODENAL STENOSIS IN DUODENAL ULCER - F.D. KODIROV; SH.SH. SAYDALIEV; D.M. KADYROV; Z.V. TABAROV (Avicenna Tajik State Medical University, 2020)
The review provides an analysis of the literary data devoted to the problem of surgical treatment of duodenal stenosis combined with ulcer penetration. Still in the scientific literature has an ambiguous interpretation of the concept of ulcer penetration: it also exceptionally includes the presence of a large ulcerative crater penetrating into a neighbouring organ with periulcerous inflammatory infiltrate. Hereby, cicatricial adhesions with neighboring organs, as the result of preceded ulcer penetration, are not considered penetration. There are controversial views among the surgeons regarding surgical tactics, volume and surgical technique. The particular situation in surgery of duodenal ulcer is domination of resection methods over organsaving techniques. There's a wrong opinion of impossibility of organ-saving surgery in penetrating duodenal ulcer. In recent years, the methods of low-invasive surgery have become increasingly popular. The analysis of literary data shows that there is insufficient knowledge of this problem, the debatability of a number of issues requiring their final solution.